Development of an External Rubber-Clay Plaster Stabilized with Alkaline Sodium Silicate to Improve Adobe Wall Rain Resistance - Wattanachai, Pitiwat; Banjongkliang, Eakphisit; Parichatprecha, Rattapoohm (Agriculture and Natural Resources, 2015)
An external clay plaster stabilized with blended prevulcanized rubber latex and sodium silicate was developed to enhance the poor water resistance of adobe walls. Sodium silicate was added to act as a pH stabilizer maintaining the pH and liquidity of the rubber latex during the manufacturing process. The study characterized the adobe plasters using an accelerated spray test, capillary absorption and microstructure investigation in terms of surface morphology, chemical analysis and porosity. The results showed that adding 3–5% sodium silicate could preserve the liquidity of 5–10% rubber latex during the mixing process. The newly developed sodium silicate + rubber-clay substrates had the highest water resistance in term of both rain resistance and water tightness, when compared with traditional clay plaster, rubber-clay plaster and stabilized rubber-clay plasters with a low sodium silicate content. The microstructure investigations confirmed that the alkaline-stabilized rubber latex could distribute throughout the substrate, was bound to most of the soil particles and filled capillary pores when dried. The stabilized-clay plaster with blended 10% rubber and 5% sodium silicate performed best, eroding only 1.2 cm after a spray test that approximated 50 yr of 1,800 mm annual rainfall, an above average annual amount for Thailand.